2001
DOI: 10.1063/1.1408587
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phosphorus-doped and boron-doped diamond-like carbon emitter arrays

Abstract: We synthesized phosphorus-doped and boron-doped emitters by using trimethylphosphite P͑OCH 3 ͒ 3 and trimethylborate B͑OCH 3 ͒ 3 as doping sources in a microwave plasma chemical vapor deposition system. Based on our experimental results from scanning electron microscopy and Raman spectra, there is much difference among undoped, phosphorus-doped, and boron-doped diamondlike material. In addition, doping both phosphorus and boron can enhance electric properties by reducing the turn-on voltage and can increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Faruque Ahmed, a͒ Effects of silver doping on the electron field emission properties of diamondlike carbon films deposited on silicon substrates by the rf reactive sputtering technique were studied in detail. [2][3][4][5][6][7][8][9] An enormous interest has been developed in the area of electron field emission property of DLC after the first direct study of field emission from a-C : H was performed by Amaratunga and Silva in 1996. The threshold field was found to decrease from 6.8 to 2.6 V / m with a variation of Ag at.…”
Section: Enhancement Of Electron Field Emission Property With Silver mentioning
confidence: 99%
See 1 more Smart Citation
“…Faruque Ahmed, a͒ Effects of silver doping on the electron field emission properties of diamondlike carbon films deposited on silicon substrates by the rf reactive sputtering technique were studied in detail. [2][3][4][5][6][7][8][9] An enormous interest has been developed in the area of electron field emission property of DLC after the first direct study of field emission from a-C : H was performed by Amaratunga and Silva in 1996. The threshold field was found to decrease from 6.8 to 2.6 V / m with a variation of Ag at.…”
Section: Enhancement Of Electron Field Emission Property With Silver mentioning
confidence: 99%
“…The threshold field was found to decrease from 6.8 to 2.6 V / m with a variation of Ag at. [5][6][7][8][9][10][11] This doping increases electron field emission at low turn-on fields by raising their Fermi level and lowering the work function of the material. The field enhancement factor was calculated and we have explained the emission mechanism.…”
Section: Enhancement Of Electron Field Emission Property With Silver mentioning
confidence: 99%
“…A large number of different techniques have evolved for the deposition of amorphous diamond like carbon films during the last two decades, the majority of the techniques reported so far involved chemical vapor deposition (CVD) [1][2][3][4]. Also, various attempts have been made to dope a:DLC films with different elements such as nitrogen [5,6], iodine [7], boron [8], phosphorous [9], fluorine [10] and metal element [11]. They showed that the doping processes significantly affect the electrical, optical and mechanical properties of a:DLC films.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, the advent of low macroscopic field emission from carbon-based films, such as diamond, diamond-like carbon (DLC), amorphous carbon (a-C), carbon nanotube/nanofibres, etc [9,10] made them the candidate materials for field emission displays. The field emission properties of DLC films are mainly dependent on the variation of chemical bonding structure other than surface roughness, and the doping of material such as boron, phosphorous, nitrogen and silicon into the DLC films [11][12][13]. One of the most effective ways to change the physiochemical properties of carbon-based material is fluorination.…”
Section: Introductionmentioning
confidence: 99%